THE EFFECT OF OLIVE OIL ON STRIAE GRAVIDARUM IN POSTPAR MOTHERS - Aisyah, Siti; Wulansari, Ika; Mursyidah, Andi (Jambura Nursing Journal, 2025)
During the period of pregnancy until delivery, a mother will experience several changes. One such change is the appearance of striae gravidarum, a form of scarring of the skin that occurs due to stretching during pregnancy. Olive oil is a rich source of fatty acids and antioxidants. The predominant fatty acid in olive oil, oleic acid, comprises 70-80%of the total fatty acids present and functions as a moisturizer. Phenolics act as antioxidants, while phenolic acids facilitate skin regeneration. Phytosterols and phytosterol esters serve as emollients for collagen elasticity, potentially assisting in the treatment of striae gravidarum. This study aimed to identify the effects of olive oil on striae gravidarum in postpartum mothers in the Limboto health centre during in three months. This study use a quantitative research design with a quasi-experimental design with a pre-test and post-test intervention and control group. The sampling technique was accidental sampling. The population under investigation comprised postpartum mothers within the Limboto Health Centre working area, with a sample size of 36 respondents. The statistical test used was the Wilcoxon test. The result demonstrated that olive oil affected striae gravidarum in postpartum mothers in the limboto Health Centre work area, with a Wilcoxon statistical test significant p-value = 0,000 (